HUBUNGAN MINAT BELAJAR DAN PEMANFAATAN SARANA PRASARANA LABORATORIUM TERHADAP HASIL BELAJAR SISWA - Nurwaddah; Alfiriani, Adlia; Novita, Rini (Information Technology Education Department, 2024)
This research aims to explore the relationship between interest in learning and use of laboratory infrastructure on the learning outcomes of class X students in informatics subjects at SMK Negeri 1 Ampek Angkek. This research is a type of survey research with quantitative methods. The sampling technique used was cluster random sampling, the number of samples in the study was taken randomly, totaling 47 students. Based on partial research results, interest in learning was obtained by t-count of 3,418>t-table of 1,678, meaning there was a significant relationship between interest in learning and learning outcomes, utilization of laboratory infrastructure was obtained by t-count of 3,148>t-table of 1,678, meaning there was a significant relationship between laboratory infrastructure and student learning outcomes. Meanwhile, simultaneously interest in learning and laboratory infrastructure shows that the calculated f value is 24,156>f-table 3.21 and the significant value is 0.000<0.05, meaning there is a significant relationship between interest in learning and the use of laboratory infrastructure on student learning outcomes. It can be concluded that interest in learning and utilization of laboratory infrastructure have a significant relationship to the learning outcomes of class.